Foreign talent : antecedents and consequences of underemployment. - Chang, Mun Wai. (2008)
This study explores the antecedents (demographic characteristics, overseas unit factor, job level factors, and personal characteristics) and consequences (work attitudes and behaviour) of underemployment among foreign talent in Singapore. One hundred and fifty-seven employees completed self-report measures of work characteristics, personal characteristics, work attitudes and behaviour.